Biology, ecology and bloom dynamics of the toxic marine dinoflagellate Pyrodinium bahamense - Gires, Usup; Asmat, Ahmad; Matsuoka, Kazumi; Po, Teen Lim; Chui, Pin Leaw (Elsevier, 2012)
It has been 40 years since the first recorded toxic bloom of Pyrodinium bahamense occurred in Papua New Guinea in 1972. Subsequently this species has increased in importance as a paralytic shellfish poisoning toxin (PSTs) producer in several regions of the world, especially in the Indo-west Pacific. P. bahamense is a thecate tropical/subtropical euryhaline dinoflagellate. Available data indicate that it forms blooms only in waters of 20 psu or higher salinity and at temperatures above 20 8C. It is monospecies with two varieties, namely var. compressum and var. bahamense. For many years it was widely accepted that only var. compressum is toxic and is limited to the tropical Pacific while var. bahamense is nontoxic and is limited to the tropical Atlantic. It is now known, however, that there are at least two locations where the varieties co-occur and it has also been proven that var. bahamense in Florida waters also produce PST. P. bahamense has a life cycle typical of many dinoflagellates. It has a heterothallic sexual cycle that produces a large spiny spherical resting cyst. The toxicity profile of P. bahamense is also very simple with most isolates producing only dc-STX, STX, neoSTX, B1 and B2 toxins. Further studies are needed in order to resolve the varietal status of the species and also to understand the environmental factors that determine its toxicity and bloom dynamics.